Faktor-Faktor Yang Mempengaruhi Penyelesaian Tugas Akhir Mahasiswa Program Studi Akuntansi Universitas Kristen Satya Wacana - Modouw, Henni Beatrix; Nugroho, Paskah Ika (Jurnal Akuntansi Profesi, 2021)
The purpose of this study was to investigate the Impact of the motivation of on-time graduation, availability of learning resources, the quality of research consultation, and peer environment to the completion of students’ research. This study was an ex-post facto research with the quantitative approach. The respondents of this study are sixty students of the Accounting Program in the Faculty of Economy of Universitas Kristen Satya Wacana who were taking the research course in the second semester of 2020/2021 period. To collect the data, questionnaires were spread in the form of google form and to analyze the data, this study used multiple regression. The result of the study showed that the motivation of on-time graduation, availability of learning resources, the quality of research consultation, and peer environment did not give positive impacts towards the completion of students’ research.